Neurological Outcome Following Late Decompression of Spinal Cord Injury at Thoracolumbar Junction (Bangladesh Journal of Neurosurgery, 2026)
Background: : Spinal cord injury is a catastrophic event that occurs as a result of spinal column disruption. Decompressive surgery of the column is performed following spinal cord injury not only to improve but also to prevent neurological impairments. There is no conclusive evidence that only early surgery improves neurological recovery or recovery is compromised by a delay of several days. Objectives: The objective of this study was to evaluate the neurological outcome of late decompressive surgery following SCI at thoracolumbar junction. Materials & Method: This single center case series analysis was conducted from 17th December 2018 to 16th December 2019 in the department of Neurosurgery, Chittagong Medical College and Hospital. Thirty one patients who were operated for SCI at thoracolumbar junction were prospectively enrolled in this study. Age, sex, associated comorbidities, mechanism of trauma, level of fractures, preoperative and follow-up American Spinal Injury Association (ASIA) grading score, time elapsed from injury to surgical treatment, preoperative magnetic resonance imaging, and surgical procedure were evaluated for each patient. After surgery patients’ were followed up and recorded ASIA score on 7th POD, 14th POD and after 6 weeks than 3rd month and 6th month after surgery. The patient populations were divided into three groups related to the timing of surgery: surgery within 4-10 days (n=11), 11-20 days (n=13) and 21-30 days (n=7) from the trauma. Results: Out of 31 patients majority (80.6%) were male and mean age was 34.9 (±11.6) years. Ten (32.3%) patients had fractures at the thoracic twelve level and 21 (67.7%) patients at lumbar one level. Before surgery 3 (9.7%), 9 (29%), 14 (42.5%) and 5 (16.1%) patients were in grade A, B, C and D respectively. After surgery, at 6 months follow up 2 (6.5%), 4 (12.9%), 7(22.6%), 9 (29%) and 9 (29%) patients were in grade A, B, C, D and E respectively. 77.5% patients showed at least one ASIA grade improvement at latest follow-up. No intra-operative complications were observed. Post-operatively, 3 (9.7%) had sacral bed sores and 2 (6.5%) had respiratory infection. Conclusion: More than two third of the patients with SCI at thoracolumbar junction had at least 1 grade improvement in 6 months following late surgical decompression.Bang. J Neurosurgery 2024; 14(1):  21-29